Putusan /Akta Perdamaian Sebagai Bagian Dari Sistem MediasiBerdasarkan Perma No. 1 Tahun 2016 Di Pengadilan NegeriPurwokerto dan Pengadilan Negeri Banyumas Tahun 2022 - Aris Priyadi (Wijayakusuma Law Review, 2022)
Settlement of civil disputes is known as a peaceful institution as stipulated in Article 130 HIR in essence, thejudge is obliged to reconcile the parties in a dispute as the basis for the implementation of the peace processin every civil case examination, but these peaceful institutions are not effective and efficient in resolving acase. dispute resolution (settlement method) out of court, known as Alternative Dispute Resolution (ADR).Perma No 1/2016, among other things, states: Every judge, mediator and parties are required to follow theprocedure for resolving disputes through mediation. Not taking the mediation procedure based on thisregulation is a violation of the provisions of Article 130 HIR/154 Rbg which results in the decision being nulland void. The Purwokerto District Court and the Banyumas District Court have in principle implemented theprovisions of PERMA No. can be resolved by a peace agreement and confirmed by a Peace Deed Decision